PIG FARMING PERFORMANCES OF THREE PAPUAN TRIBES: CASE STUDY OF BYAK, ONATE AND ARFAK TRIBES IN PAPUA BARAT - Iyai, D.A.; Marani, O.; Marjen, T.; Usior, I. (Diponegoro University, 2013)
The objective of this study was to depict the pig farming performances of three different nativePapuan tribes, i.e. Byak, Onate and Arfak. Sites in Biak were taken from Samofa District. Sites in Yapenwere taken from South Yapen District comprised of Famboaman, Anotaurei, Mariadei and Mantembuvillages. Site in Manokwari was chosen at Sub-district of Wosi. Participatory research using interviewand observation was done towards 105 pig farmers. One-way analysis of variance and Pearson Chisquare(χ2) were used to analyse data. Several indicators tested were age, education, objectives ofrearing pigs, and species of pigs. The characteristics of pig farmers were similar. The variations of pigfarmers’ characteristics ware found in pigs’ rearing experience, animal number and litter size. Offeredfeeding on each physiological period was different. Similar finding were feeding sources and feedingprocess. Reproduction knowledge and their experience in farrowing management are similar amongstthe tribes. In general experiences and knowledge to prevent infectious diseases in general were similar.The three tribes have relatively similar in managing their pig farming systems.